Specific Disruption of Abca1 Targeting Largely Mimics the Effects of miR-33 Knockout on Macrophage Cholesterol Efflux and Atherosclerotic Plaque Development. Issue 6 (15th March 2019) - Price, Nathan L.; Rotllan, Noemi; Zhang, Xinbo; Canfrán-Duque, Alberto; Nottoli, Timothy; Suarez, Yajaira; Fernández-Hernando, Carlos
Abstract : Rationale: : Inhibition of miR-33 reduces atherosclerotic plaque burden, but miR-33 deficient mice are predisposed to the development of obesity and metabolic dysfunction. The proatherogenic effects of miR-33 are thought to be in large part because of its repression of macrophage cholesterol efflux, through targeting of Abca1 (ATP-binding cassette subfamily A member 1). However, targeting of other factors may also be required for the beneficial effects of miR-33, and currently available approaches have not allowed researchers to determine the specific impact of individual miRNA target interactions in vivo. Objective: : In this work, we sought to determine how specific disruption of Abca1 targeting by miR-33 impacts macrophage cholesterol efflux and atherosclerotic plaque formation in vivo. Methods and Results: : We have generated a novel mouse model with specific point mutations in the miR-33 binding sites of the Abca1 3'untranslated region, which prevents targeting by miR-33. Abca1 binding s ite mutant ( Abca1 BSM ) mice had increased hepatic ABCA1 expression but did not show any differences in body weight or metabolic function after high fat diet feeding. Macrophages from Abca1 BSM mice also had increased ABCA1 expression, as well as enhanced cholesterol efflux and reduced foam cell formation. Moreover, LDLR (low-density lipoprotein receptor) deficient animals transplanted with bone marrow from Abca1 BSM mice had reduced atherosclerotic plaque formation, similar to mice transplanted with bone marrow from miR-33 knockout mice. Conclusion: : Although the more pronounced phenotype of miR-33 deficient animals suggests that other targets may also play an important role, our data clearly demonstrate that repression of ABCA1 is primarily responsible for the proatherogenic effects of miR-33. This work shows for the first time that disruption of a single miRNA/target interaction can be sufficient to mimic the effects of miRNA deficiency on complex physiological phenotypes in vivo and provides an approach by which to assess the impact of individual miRNA targets. Abstract : Supplemental Digital Content is available in the text.